Sobolev-type theorem for commutators of Hardy operators in grand Herz spaces - Sultan, Babar; Sultan, Mehvish (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC 517.5 The higher-order commutators of fractional Hardy-type operators of variable order ζ(z) are shown to be bounded from the grand variable Herz spaces K ^a(·), u),θ_ p(·)(R^n) into the weighted space K ^a(·), u),θ_ρ, q(·)(R^n), where ρ=(1+|z_1|)^-λ and 1 q(z)=1 p(z)-ζ (z) n if p(z) is not necessarily constant at infinity.